A dinâmica na caracterização do timbre na Música para Trompete Solo, de Estércio Marquez Cunha - Costa, Alessandro da (2015)
This paper, divided into Part A and Part B, investigates how dynamics influences the timbre in the Música para Trompete Solo by Estercio Marquez Cunha. The approach of the nuances of the timbre in this piece of music is not only directed towards what determines the recognition of the sound of the instrument, but also to its interpretation. To understand the relations between these two sound parameters in this piece, first, as explained in Part B, it is made one review of the literature about the timbre and the dynamic in a musical context. Then, there is a phenomenological analysis of Música para Trompete Solo with the intention of knowing the structure of the piece, and finally, the interpretative suggestions, the time which aim to verify how dynamic, interacting with other elements of composition, act in the configurations of the timbre in this piece by Estercio Marquez Cunha. The end result was the interpretation of the piece in two recitals, as shown in the programs contained in Part A.